Early Intervention Referral and Enrollment Among Infants with Neonatal Abstinence Syndrome. Issue 6 (July 2019) - Peacock-Chambers, Elizabeth; Leyenaar, JoAnna K.; Foss, Sheila; Feinberg, Emily; Wilson, Donna; Friedmann, Peter D.; Visintainer, Paul; Singh, Rachana
ABSTRACT: Objective: To identify factors associated with referral and enrollment in early intervention (EI) for infants with neonatal abstinence syndrome (NAS). Methods: We conducted a retrospective cohort study of 256 infants born with NAS (2006–2013) at a tertiary care hospital in (Springfield), Massachusetts, linking maternal-infant birth hospitalization records with Department of Public Health EI records. We calculated the percent of infants retained at each step in the EI enrollment process over the first 3 years of life. We conducted separate multivariable logistic regression analyses to identify factors associated with EI referral and enrollment. Results: Among mothers, 82% received medication-assisted treatment at delivery, 36% endorsed illicit drug use during pregnancy, and 76% retained custody of their child at discharge. Among infants, 77% were referred to EI and 48% were enrolled in services. Of infants discharged to biological parents, 81% were referred to EI versus 66% of infants discharged to foster care ( p ⩽ 0.05); this difference persisted in multivariable analysis [adjusted odds ratio, 2.30; 95% confidence interval (CI), 1.09–4.86]. Infants in the highest tertile for length of stay had 2.70 times the odds of EI enrollment (95% CI, 1.37–5.31). Conclusion: Fewer than half of the eligible infants with NAS were enrolled in EI services. Discharge to a biological parent and longer hospital stay had the strongest associations with EI referral and enrollment, respectively. Efforts to improve EI referral rates during the birth hospitalization, particularly among infants discharged into foster care, and close follow-up for infants with shorter hospital stays would enhance the developmental supports for this vulnerable population.